THE INCREASE OF GROWTH RATE AND PROTEIN CONTENT OF GOURAMI (OSPHRONEMUS GOURAMY LAC.) FED ON DIETS CONTAINING EARTHWORM (LUMBRICUS RUBELLUS) - Siswanthi
Abstract : Growth and protein tissue content in gourami (Osphronemus gouramy Lac.) have been studied by feeding diet containing earthworm (Lumbricus rubellus). Studies were performed on 5-6 month old gourami, with initial weight 15-16 g and length 10,5 11,5 cm. The experiment consisted of treatment groups and control. The treatment groups were fed diets containing 10%, 20%, 30% and 40% powdered earthworm, whereas no earthworm was added in the diet for control fish. They were fed diet at 10% of body weight per day for eight weeks. Uneaten diet was collected 3 hours after feeding and faeces collection was done on the next day. The uneaten diet and faeces were dried to determine the dried weight. The body weight was measured once a week. The protein tissue content and intestine protease activity were determined on day-0, -28 and -56. Compared to controls, results showed that addition of earthworm significantly increased (p<0,05) the average of body weight, feed intake, specific growth rate and feed efficiency; however there were no significant different among treatments. Highest average feed efficiency (24,84%) was showed in fish given 10% earthworm diet. Whereas all the other parameters showed the highest value on fish treated with 30% earthworm diet. Average absorption efficiency was not significantly different among treatments and control; the highest value (96,05%) was showed by 30% earthworm diet. The protein tissue content tend to increase on every treatment, and on every observation; the highest value (0,49 g protein/ g tissue) was obtained on the day -56 by 40% earthworm diet. The addition of earthworm did not significantly influence the intestine protease activity and tend to increase on day-56 among treatment. It can be concluded that the diet containing earthworm increases body weight, growth rate, feed intake and feed efficiency; the highest value is showed on fish given 30% earthworm diet, while 10% earthworm diet gives the highest feed efficiency. The addition of earthworm tends to increase protein tissue content, but not significantly influence the absorption efficiency and intestine protease activity.